1952
DOI: 10.1152/ajplegacy.1952.170.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Tissues Excised From Thyroxine-Injected Rats

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
2
2

Year Published

1957
1957
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(85 citation statements)
references
References 0 publications
7
74
2
2
Order By: Relevance
“…The most prominent effects of T $ on ANT2 mRNA expression were observed in heart and liver, whereas weak or no responses occurred in kidney and brain. This tissue-specific T $ response on ANT mRNA shows a striking similarity to the tissue-specific changes in respiratory metabolism [1,2] and thus suggests that ANT2 is important in modulating T $ -induced oxygen consumption.…”
Section: Discussion Expression and T 3 -Dependent Regulation Of Antmentioning
confidence: 67%
See 1 more Smart Citation
“…The most prominent effects of T $ on ANT2 mRNA expression were observed in heart and liver, whereas weak or no responses occurred in kidney and brain. This tissue-specific T $ response on ANT mRNA shows a striking similarity to the tissue-specific changes in respiratory metabolism [1,2] and thus suggests that ANT2 is important in modulating T $ -induced oxygen consumption.…”
Section: Discussion Expression and T 3 -Dependent Regulation Of Antmentioning
confidence: 67%
“…T $ administration to rats leads to a marked increase in oxygen consumption after 36-72 h in tissues such as heart, liver and kidney, whereas no effects occur in spleen, testes and adult brain (see, for example, [1]). This stimulation of respiration seems to be the result of an increased capacity of both the respiratory chain and oxidative phosphorylation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for many years, the impact of thyroid disorders on male reproduction remained controversial. Early studies in the 1950's demonstrated that testes were essentially independent of thyroid hormone effects (1,2). For this reason, the potential of thyroid hormone in the modulation of male reproductive function was not determined.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the development of a hyperthyroid state in vertebrates leads to an increase in their metabolic rate due to an enhanced rate of O 2 consumption in most of body tissues (Barker and Klitgaard, 1952). Although thyroxine (T 4 ) is the main product of thyroid secretion is widely shared the view that T 4 is only a prohormone and must be activated by deiodination to triiodothyronine (T 3 ) in order to initiate thyroid hormone action.…”
Section: Introductionmentioning
confidence: 99%